Coverage of nutrition and health interventions in West Bengal: Insights from the National Family Health Survey-4 - Sehgal, Mrignyani; Nguyen, Phuong Hong; Avula, Rasmi; Scott, Samuel P.; Menon, Purnima (International Food Policy Research Institute, 2018)
This Data Note describes the coverage of a set of key nutrition and health interventions. The findings here are based on data from the National Family Health Survey 2015-2016. Indicators to capture the coverage of the interventions here are all calculated for women (15-49 years) with a child under five years of age. All analyses are based on the last-born child for each woman and indicator definitions are provided in Annex 1 of this Note. For some indicators, age categories may vary.